Gestational Diabetes and Longitudinal Ultrasonographic Measures of Fetal Growth in the NICHD Fetal Growth Studies-Singletons (P11-133-19) - Li, Mengying (Curr Dev Nutr, 2019)
OBJECTIVES: Gestational diabetes (GDM) is associated with increased risk for large-for-gestational-age birth. Yet, longitudinal fetal growth trajectories in women with GDM and the timing of alterations related to GDM is not well understood, particularly in early pregnancy. This study aims to investigate these critical data gaps. METHODS: The NICHD Fetal Growth Studies–Singleton Cohort enrolled women at 8w0d to 13w6d gestation from 12 U.S. clinical centers and randomized them among four ultrasonology schedules for longitudinal fetal measurement. Fetal biparietal diameter, head circumference (HC), abdominal circumference (AC), femurs length and humerus length were measured. Estimated fetal weight (EFW) was calculated using the Hadlock formula. GDM was defined using the Carpenter-Coustan Criteria, impaired glucose tolerance (IGT) was defined as 2-hour plasma glucose in the 75 g or 100 g oral glucose tolerance test (OGTT) 140–199 mg/dL, and normal glucose tolerance (NGT) was defined by no elevated values on either the OGTT or 50 g glucose challenge test. The fetal growth trajectories were modeled using linear mixed models with cubic spline adjusting for race, age, parity, pre-pregnancy BMI and infant sex. RESULTS: One hundred and seven women developed GDM, 118 developed IGT, and 2,020 had NGT. Most fetal growth measures were larger at 10–12 weeks and became smaller at 14–16 weeks in GDM than NGT group. At 28 weeks, AC and EFW became larger in GDM group, and the differences persisted through 40 weeks (at 40 weeks: AC: 368 vs. 355 mm, P = 0.03; EFW: 3866 vs. 3558 g, P = 0.003). The HC to AC ratio was smaller in GDM group 19–36 weeks. The associations were modified by the family history of diabetes (p-interaction < 0.001), such that GDM-related early pregnancy growth alterations were only seen in women with a family history of diabetes, whereas GDM-related late pregnancy overgrowth was only seen in those without. IGT group also had larger EFW and smaller HC to AC ratio than the NGT group at late third trimester. CONCLUSIONS: GDM-related fetal growth alterations appeared to start as early as 10 weeks of gestation. Fetal overgrowth related to GDM was solely driven by AC and started at 28 weeks of gestation, suggesting current GDM diagnosis and treatment timing may be too late to normalize fetal growth. FUNDING SOURCES: Eunice Kennedy Shriver National Institute of Child Health and Human Development. SUPPORTING TABLES, IMAGES AND/OR GRAPHS: